Integration of virtual platforms for enhanced conference experience: Data-based evidence from the Society of Interdisciplinary Placebo Studies 2021 conference - Cornell, Jessica; Taj, Ariana; Sivinski, John; Yin, Margaret; Bhatia, Parth; Oula, Desai; Fatschel, Sophia; Franklin, Patricia; Noel, Jason; Colloca, Luana; Seneviratne, Chamindi (Frontiers in Communication, 2022)
Background: The Society of Interdisciplinary Placebo Studies (SIPS) was one of many organizations that hosted a virtual scientific conference in response to the COVID-19 pandemic restrictions. This article reports on the methods used to design and analyze an engaging, virtual scientific conference in 2021, while retaining essential benefits of an in-person conference experience, along with the findings and implications for future meetings. Methods: Participant use of and interaction with different features of the conference platform were recorded and exported for analysis. Additionally, all SIPS conference attendees were invited to complete a brief, online post-conference survey that inquired about their perceptions of the SIPS conference specifically as well as their opinions of virtual and hybrid conferences in general. Using these data, we assessed (1) attendance patterns, (2) level of engagement, and (3) attendee satisfaction. Results: The platform recorded 438 unique, active conference attendees who used either a mobile app, web browser, or both to participate during the three-day program. Seventy-four percent (N=324) of active users attended all three days with 30 and 26 new attendees on Days 2 and 3, respectively. The connections feature offered on the platform was the most utilized function within the online forum. Attendance in the parallel workshop sessions remained constant across the three days, with an average of 44.6% (SD =6.77) of people moving between workshops within a single session. The two poster sessions had an average of 47.6 (SD = 17.97) and 27.8 (SD = 10.24) unique views per poster, respectively. Eleven percent (N=48) of attendees completed the post conference survey. Thirty-six percent of these responders stated they were only able to attend because the conference was offered virtually. Further, the quality of the conference had an average satisfaction rating of 68.08 out of 100 (SD = 22.94). Conclusion: Results of data analyses suggest the virtual platform allowed for those who were unable to attend to join virtually, produced moderate engagement throughout the conference, and that the majority of attendees were satisfied with the quality of the fully virtual conference. Therefore, incorporating virtual aspects in future in-person conferences could enhance conference experience and participation.